(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
COVID-19 has impacted the lives of each and every person in the world. Diagnosis of COVID-19 using imaging systems can be integrated with the standard Reverse Transcription Polymerase Chain Reaction (RT PCR) test to perform the diagnosis more accurately. In this paper, transfer learning based method using a pre-trained deep neural network model viz., ResNet is proposed to classify COVID-19 computed tomography (CT) lung images. The pre-trained model is fine-tuned in order to make it learn the features specific to COVID-19 CT lung images. The proposed method is compared with the methods available in the literature. The results show that the proposed method is comparable to the existing methods.